"Wild Worship of a Lost and Buried Past": Enchanted Archaeologies and the Cult of Kata, 1908–1924. (15th June 2017) - Wickstead, Helen
Histories of archaeology traditionally traced the progress of the modern discipline as the triumph of secular disenchanted science over pre-modern, enchanted, world-views. In this article I complicate and qualify the themes of disenchantment and enchantment in archaeological histories, presenting an analysis of how both contributed to the development of scientific theory and method in the earliest decades of the twentieth century. I examine the interlinked biographies of a group who created a joke religion called "The Cult of Kata". The self-described "Kataric Circle" included notable archaeologists Harold Peake, O.G.S. Crawford and Richard Lowe Thompson, alongside classicists, musicians, writers and performing artists. The cult highlights the connections between archaeology, theories of performance and the performing arts – in particular theatre, music, folk dance and song. "Wild worship" was linked to the consolidation of collectivities facilitating a wide variety of scientific and artistic projects whose objectives were all connected to dreams of a future utopia. The cult parodied archaeological ideas and methodologies, but also supported and expanded the development of field survey, mapping and the interpretation of archaeological distribution maps. The history of the Cult of Kata shows how taking account of the unorthodox and the interdisciplinary, the humorous and the recreational, is important within generously framed approaches to histories of the archaeological imagination. The work of the Kataric Circle is not best understood as the relentless progress of disenchanted modern science. It suggests a more complicated picture in which dynamics of enchantment and disenchantment stimulate and discipline the imagination simultaneously. I conclude with a reexamination of the politics of an emphasis on playfulness and enchantment.